2015
DOI: 10.5539/jas.v7n9p154
|View full text |Cite
|
Sign up to set email alerts
|

Selection for High Yield and Stability among Early Maturing Greengram Genotypes

Abstract: Greengram, Vigna radiata (L.) Wilczek is an important source of proteins and micronutrients to small holder farmers in eastern and northern regions of Uganda. Most of the landraces currently grown by small scale farmers are characterized by low yields and late maturity. In order to identify high yielding and stable varieties, an experiment was conducted to evaluate the yield performance of introduced early maturing genotypes from the World Vegetable Centre (AVDRC) in seven locations of Uganda. Yield performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This is in agreement with a recent study by Mbeyagala et al (2015) in which a yield stability statistic (YS i ) proposed by Kang (1993) identified the same genotypes (G2, G1, G4 and G6) as being high yielding and stable.…”
Section: Resultssupporting
confidence: 82%
“…This is in agreement with a recent study by Mbeyagala et al (2015) in which a yield stability statistic (YS i ) proposed by Kang (1993) identified the same genotypes (G2, G1, G4 and G6) as being high yielding and stable.…”
Section: Resultssupporting
confidence: 82%
“…2 and 3). Among the preferred genotypes were Filsan and Sunshine, that had also been identified in two previous studies (Mbeyagala et al, 2015;Mbeyagala et al, 2016) as high yielding and stable across environments. Genotypes such as blackgram and yellowgram that yielded higher than all the other genotypes (Table 3), were not preferred by farmers.…”
Section: Discussionmentioning
confidence: 58%